Small world application layer for ad hoc networks - Trajanov, Dimitar; Filiposka, Sonja; Makraduli, Jani; Grnarov, Aksenti (My University, 2003)
A mobile ad hoc network is an autonomous system of mobile entities connected by wireless links. Nodes in an ad hoc network can act as both hosts and routers given that they can both generate and forward packets. Since there is no existing communication infrastructure (e.g., a wired or a fixed wireless base station), all entities are free to move while creating a self-organizing dynamic network. Ad hoc networks are suited for use in situations where infrastructure is either not available, not trusted, or should not be relied on in times of emergency. A few examples include: military solders in the field; an infrastructure-less network of notebook computers in a conference or campus setting; the forestry or lumber industry; space exploration; undersea operations; and temporary offices such as campaign headquarters [1]. The people that come together and form an ad hoc network in order to share information are also part of some social network. Since most human communication takes place directly between individuals, such networks are crucially important for communications. This sociological concept is the basis for small world research, which describes the tendency for each entity in a large system to be separated from any other entity in the system by only a few steps [2]. Small world networks are promising candidates for communication networks since data-flow patterns show a large amount of clustering with a small number of "longdistance" communications that need to be accomplished efficiently [12]. This is a result of the fact that people tend not so much to have friends as to have groups of friends, each of which is like a little cluster based on shared experience, location, or interests (see Fig 1.). This groups are joined to each other by the overlaps created when individuals in one group also belong to other groups [3]. Most of the communication between the entities is done inside the friends cluster while the necessity to communicate with a non friend is scarcely rare. In most of the articles on ad hoc network performances traffic in a randomly connected nodes environment is considered. Examples can be found in [4][5]0. Johansson et al. [7] made a performance analysis by simulating three realistic scenarios that include rescue operations in remote areas, ad-hoc networks between notebook computers used to spread and share information among the participants of a conference; and short range ad-hoc network intercommunication of various mobile devices (e.g., a cellular phone or PDA). For the purposes of investigating the performances of ad hoc networks in [8] an application layer with clustering is used and in [9] the effects of small world phenomena on performances of ad hoc networks is performed. In this paper we propose a new realistic model for application layer in ad hoc networks.